Tracing the Trophic Fate of Aquafeed Macronutrients With Carbon Isotope Ratios of Amino Acids - Larsen, Thomas; Wang, Yiming V.; Wan, Alex H. L. (Frontiers in Marine Science, 2022)
To meet future seafood demands, ingredients derived from algae and other novel and sustainable sources are increasingly being tested and used as replacers to traditional aquafeed ingredients. Algal ingredients in particular are being promoted for their sustainability and their additional functional attributes in farmed aquatic animals. Test on algal supplemented aquafeeds typically focus on a suite of immunological and physiological indicators along with fish growth performance or muscle quality. However, to optimize the replacement of fish meal with algal derived ingredients, it is crucial to understand the metabolic fate in the algal macronutrients (carbohydrates, fats, and proteins), and their nutritional interactions with other ingredients after ingestion. Here, we assess the potential of using the emerging technology- stable carbon isotope (δ13C) analysis of single amino acids (AAs) as a nutritional biomarker in aquaculture. Applications of δ13CAA-based approaches in feeding trials show promise in closing the knowledge gap in terms of understanding how fish and other aquaculture taxa assimilate and metabolize algal derived macronutrients. Source diagnostic δ13C fingerprints among the essential AAs can trace the protein origins to broad phylogenetic groups such as red macroalgae, brown macroalgae, bacteria, and terrestrial plants. Among the non-essential AAs, δ13C patterns have the potential to inform about metabolic routing and utilization of dietary lipids and carbohydrates. Despite the potential of δ13CAA as a nutritional biomarker, the few applications to date in fish feeding trials warrant further development and implementation of δ13CAA-based approaches to improve understanding of protein origins and macronutrient metabolic routing.